Low-carbon high-performance white cementing material and preparation method thereof

By adopting the combination of S95 mineral powder, gypsum, white silicate cement clinker, lithium slag, white filler and composite active exciter, and grinding through a ball mill, the problems of large energy consumption and high carbon emissions caused by high temperature calcination in the production process of white silicate cement materials are solved, and low-carbon and high-performance white gelling materials are achieved.

CN119874224APending Publication Date: 2025-04-25CHANGZHOU GREEN MART CONSTR TECH CO LTD +1
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202510059301.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-15
Publication Date
2025-04-25

AI Technical Summary

Technical Problem

In the prior art, white silicate cement materials need to be calcined at high temperature during the production process, resulting in large energy consumption, large carbon emissions, and low product strength, high alkalinity and large shrinkage, which poses the risk of alkalinity and cracking.

Method used

A low-carbon and high-performance white gelling material is used, and its raw material components include S95 ore powder, gypsum, white silicate cement clinker, lithium slag, white filler and composite active exciter. It is grinded by a full-circuit planetary ball mill to form a gelling material with high strength, low alkali, low shrinkage and high whiteness.

Benefits of technology

It realizes low-carbon cement production without high temperature calcination, low energy consumption and low carbon emissions. The product has the performance advantages of high strength, low alkali, low shrinkage and high whiteness. It is suitable for decoration and large-volume products to avoid the risks of pan-alkali and cracking.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005242377520000081
    Figure BDA0005242377520000081
  • Figure BDA0005242377520000091
    Figure BDA0005242377520000091
  • Figure BDA0005242377520000092
    Figure BDA0005242377520000092
Patent Text Reader

Abstract

The invention relates to a low-carbon high-performance white cementing material which is prepared from the following raw material components in percentage by weight: 50-80% of S95 mineral powder, 12-20% of gypsum, 3-6% of white Portland cement clinker, 1-5% of lithium slag, 10-30% of white filler and 0.2-0.8% of a composite active excitator.The preparation method comprises the following steps: weighing the raw materials in proportion, uniformly mixing the raw materials, and preparing the low-carbon high-performance white cementing material. And grinding all the raw materials in an omnibearing planetary ball mill for 60 minutes to obtain the low-carbon high-performance white cementing material. The production process is simple, only a one-step grinding process is needed, calcination is not needed, and the carbon emission is greatly reduced compared with that of traditional cement production. The raw materials are wide in source, a large amount of solid waste is utilized, the slag, the ardealite and the lithium slag are utilized, the total amount of the waste high-temperature ceramic whiteware powder is 90% or above, cost is low, and the environment-friendly cyclic sustainable development significance of solid waste utilization is achieved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the field of low-carbon cementitious materials, in particular to a high-strength, low-alkali, low-shrinkage white cementitious material with low carbon significance that can be produced by utilizing a large amount of solid waste materials without high-temperature calcination and a preparation method thereof. Background Art

[0002] As the world pays more and more attention to energy conservation, environmental protection and sustainable development, the building materials industry is facing an urgent need for transformation and upgrading. Traditional cement production has high energy consumption and large carbon emissions, and has become one of the important sources of global greenhouse gas emissions. It is estimated that the production of 1 ton of cement consumes about 95 kg of standard coal, 1.5 tons of limestone, and emits 0.43 tons of CO. 2 , in the anthropogenic CO 2 Cement production accounts for 5% to 7% of China's total cement production. Therefore, the research and development of low-carbon, high-performance new cement materials has become a hot topic in the current building materials field.

[0003] White Portland cement refers to a hydraulic cementitious material made by grinding white Portland cement clinker with low iron oxide content, appropriate amount of gypsum and mixed materials (limestone and kiln dust), referred to as white cement. Among them, in order to ensure whiteness, white Portland cement clinker should use relatively pure raw materials, such as pure kaolin, pure quartz sand, pure lime or chalk, and burn the clinker at a higher temperature (1500℃~1600℃). The production process consumes a lot of energy and has more carbon emissions than ordinary cement. White Portland cement is widely used in modern times, mainly used for building decoration, such as floors, stairs, steps, exterior wall facings, colored water-brushed stone and terrazzo manufacturing, facing mortar, artificial stone, cement roughening technology, marble and tile inlay, concrete sculpture craft products, etc., as well as for the manufacture of colored cement, etc. However, due to the limitation of the chemical composition of Portland cement itself, its reaction product contains a large amount of calcium hydroxide, resulting in high alkalinity. It is easy to cause alkali problems in the decoration field, affecting the decorative effect. In addition, white cement has a large shrinkage, and there is a risk of shrinkage cracking when used in the production of large white components or large panels, causing safety hazards and economic losses.

[0004] At present, there are not many studies on new white cementitious materials in China, and the performance of related products is not excellent enough. CN108793782B discloses a white cement made from industrial waste slag and alkali slag and its preparation method. The preparation method includes the step of drying and roasting at 800 degrees, which still consumes a lot of energy and has a large carbon emission. In addition, the product performance does not have the advantages of low alkali and low shrinkage, and the upper limit of strength is not high. The 3-day flexural strength is 4.6 MPa, the 3-day compressive strength is 26.7 MPa, the 28-day flexural strength is 7.9 MPa, and the 28-day compressive strength is 53.1 MPa. Compared with the 3-day flexural strength of 6.8 MPa, the 3-day compressive strength of 42.0 MPa, the 28-day flexural strength of 8.8 MPa, and the 28-day compressive strength of 64.0 MPa of Albo 525 white cement, there is no advantage in strength.

[0005] CN103819105B discloses an ecological high-strength modified white cement and a preparation method thereof, wherein a large amount of burnt lime and sodium silicate are added. The alkalinity of the product is high, and the shrinkage performance is not mentioned. The strength is also significantly lower than that of the commercially available 525 white cement. Summary of the invention

[0006] The technical problem to be solved by the present invention is: in order to overcome the deficiencies in the prior art, a low-carbon high-performance white gelling material and a preparation method thereof are provided.

[0007] The technical solution adopted by the present invention is: a low-carbon high-performance white cementitious material, the raw material components of which are as follows by weight: 50-80% of S95 mineral powder, 12-20% of gypsum, 3-6% of white silicate cement clinker, 1-5% of lithium slag, 10-30% of white filler, and 0.2-0.8% of composite active activator;

[0008] After further optimization, the weight percentage of each component is: S95 mineral powder 60-70%, gypsum 14-16%, white silicate cement clinker 3-5%, lithium slag 3-5%, white filler 10-15%, and composite active activator 0.6-0.8%.

[0009] Furthermore, the performance of the S95 mineral powder described in the present invention must meet the requirements of the S95 mineral powder in the standard GB / T 18046-2017 "Granulated blast furnace slag powder for cement, mortar and concrete". In addition, since the whiteness requirement of the final product is not low, the Hunter whiteness of the S95 mineral powder itself should be greater than or equal to 85. Since the iron content will affect the color of the material, its Fe 2 O 3 It should be less than or equal to 0.6%. Through a large number of experimental studies, it is found that the Al content in S95 ore powder 2 O 3 The content greatly affects the sulfate activation and low-alkali activation effects. To ensure high strength, Al 2 O3 The content should be greater than or equal to 12%

[0010] Furthermore, the white Portland cement clinker described in the present invention should meet the requirements of GB / T 2015-2017 "White Portland Cement".

[0011] Furthermore, the gypsum described in the present invention is a mixed gypsum of natural anhydrite and white phosphogypsum after chemical impurity removal in a ratio of 1:3. Since phosphogypsum contains impurities such as phosphorus, its dissolution rate in water is very slow. In contrast, the dissolution rate of natural anhydrite is faster. Replacing phosphogypsum with part of natural anhydrite can significantly accelerate the early reaction rate of white cementitious materials and improve the early strength. The natural anhydrite used should meet the requirements for anhydrite in GB / T5483-2008 "Natural Gypsum", and the quality should be selected as level one. The phosphogypsum used should meet the requirements in GB / T 23456-2018 "Phosphogypsum", and the level one index requirements should be selected.

[0012] Furthermore, the lithium slag described in the present invention is an industrial residue produced by producing lithium carbonate using a sulfuric acid method after calcining spodumene at a high temperature of 1000-1200°C, and its main chemical components are SiO 2 and Al 2 O 3 The total content of the two is greater than 60%, showing high pozzolanic activity. It is necessary to meet the relevant requirements of YB / T 4230-2010 "Lithium slag powder used in cement and concrete".

[0013] Furthermore, the white filler described in the present invention is waste high-temperature white ceramic waste, the main component of which is SiO 2 and Al 2 O 3 , and a small amount of CaO, which has certain volcanic ash activity and high whiteness. After ultra-fine grinding, the whiteness is very high and the activity is further improved. On the one hand, as a filler, it can effectively increase the overall whiteness of the product, and on the other hand, it can promote the hydration reaction and improve the strength.

[0014] The composite active activator used in the present invention is a mixture of a nano-crystal seed early strength agent and an alkali metal lactate, specifically a mixture of nano-calcium silicate hydrate powder and sodium lactate powder in a mass ratio of 1:2. Nano-calcium silicate hydrate powder can provide nanoparticles as reactive centers, reduce the barrier to the formation of calcium silicate hydrate gel, promote the rapid formation of calcium silicate hydrate gel, and improve the early strength of the cementitious material. The lactate anion ionized by sodium lactate dissolved in water is a metal cation chelating agent, which can form a water-soluble complex with the metal cation in the slag glass, which is very beneficial to the continuous hydrolysis of the slag glass in the later stage, can promote the formation of calcium sulfonate and CSH, make the hardened slurry structure more compact, and further improve the later strength of the cementitious material.

[0015] A method for preparing a low-carbon, high-performance white gelling material, comprising the following specific steps:

[0016] Weigh S95 mineral powder, gypsum, white silicate cement clinker, lithium slag, white filler and composite active activator in proportion, mix these raw materials evenly, and then put all the raw materials into a full-range planetary ball mill for grinding, set the speed to 300r / min, the ball-to-material ratio to 8:1, the grinding time to 60min, and grind to a specific surface area of ​​800m 2 / kg to obtain low-carbon high-performance white gelling material.

[0017] The technical principle of the present invention is:

[0018] The silicon-oxygen and aluminum-oxygen tetrahedrons in the S95 ore powder are the main material basis of the cementitious material CSH. The white silicate cement clinker provides the alkalinity of the system, and gypsum is used as an activator. In an alkaline environment, the nSiO 2 ·mAl 2 O 3 qCaO reacts with calcium hydroxide and gypsum to form hydrated calcium silicate and ettringite. Under alkaline conditions, ettringite is a complex salt with extremely low solubility, and its solubility product constant is 10-111.6. After the reaction, it quickly precipitates in the form of crystals, which breaks the dissolution balance between aluminosilicate minerals and soluble aluminum in the solution, accelerates the dissolution of aluminum in aluminosilicate minerals, and accelerates the dissociation of aluminum oxygen tetrahedrons from the polymer of silicon (aluminum) oxygen tetrahedrons, and then repolymerizes to form hydrated calcium silicate (aluminum) gel. The needle-shaped ettringite crystals in the hydration product overlap each other and fill in the hydrated calcium silicate. At the same time, other unhydrated particles will also fill in the pores of the hydration product, and finally form a hydrated hardened body of the cementitious material.

[0019] Calcium sulfate complex salt forms needle-rod crystals with nanometer diameter, which has a strengthening and toughening effect on the hardened body. By utilizing the synergistic excitation effect of cement clinker, gypsum powder and slag powder, a large number of needle-rod complex salt crystals are formed, and a large number of nearly amorphous CSH gels and zeolite phases are also formed, which tightly wrap the needle-rod complex salt crystals, greatly improving the stability of the entire system.

[0020] The addition of a small amount of lithium slag can shorten the setting time and improve the early strength. This is because Al in lithium slag 2 O 3 The content is above 20%, and it also contains a large amount of amorphous SiO 2, and its active ingredient content is higher than that of mineral powder. Lithium slag is more grindable than mineral powder. Under the same grinding time, lithium slag can be ground finer and more active. Lithium slag is a porous structure with a large internal surface area and strong adsorption capacity. It can quickly adsorb various ions and react. The above factors make the reaction rate of lithium slag faster than that of slag, and it generates hydrated calcium silicate and calcium aluminate crystals first, which in turn promotes the hydrolysis of slag, thereby shortening the overall setting time and improving the early strength.

[0021] Nano-calcium silicate hydrate powder in the composite active activator can provide more nucleation sites for the growth of hydration products, promote the formation of calcium silicate hydrate gel, and generate more hydration products, which overlap with each other, fill the large pores and refine the small pores, making the hardened slurry structure more uniform and dense, thereby significantly improving the early strength; in the later stage of hydration, the lactate anion of the bidentate ligand produced by the hydrolysis of sodium lactate has a chelating effect and can form a water-soluble complex with the metal ions in the slag glass, destroying the glass structure, promoting the dissolution of the unreacted slag particles, generating more calcium sulfonate and CSH gel, optimizing the pore structure, and greatly enhancing the later strength.

[0022] The above process is essentially a chemical excitation of the mineral powder. The present invention also has a physical excitation method. The various raw materials are mixed by grinding and then ultra-finely ground to make the raw material particles ultra-fine. This is a physical excitation method that effectively improves the activity of the mineral powder. Ultra-fine is not only a process of reducing the particle size, but also its crystal structure and surface will undergo significant changes. Along with the grinding process, the lattice bond energy of the mineral powder decreases, the grain size decreases, the crystal deformation increases, the structure is distorted, the specific surface area is larger, and more reaction surfaces are exposed. Its microscopic filling effect and activity are higher. It accelerates the dissociation and repolymerization of silicon oxygen and aluminum oxygen tetrahedrons in the mineral powder in an alkaline environment, promotes the formation of early hydration products, changes the microscopic morphology of the hydration products, and has a significant impact on the mechanical properties and durability of the hardened body.

[0023] Compared with the prior art, the present invention has the following advantages:

[0024] 1. The low-carbon high-performance white cementitious material of the present invention only needs one production process, and all raw materials can be ground together. No calcination is required during the production process, and the amount of clinker used is extremely small. It is a low-carbon cement that does not require high-temperature calcination, has low energy consumption, and has low carbon emissions. Compared with traditional white cement, it has better performance in all aspects and lower cost. It has broad application prospects in waterproof coatings, terrazzo, artificial stone, caulking agents, adhesives, white concrete products, decorations, etc., and has important practical significance;

[0025] 2. The raw materials are widely sourced and a large amount of solid waste is used. The total amount of slag, phosphogypsum, lithium slag and waste high-temperature white porcelain powder is more than 90%. It is not only low-cost, but also has the significance of green recycling and sustainable development of solid waste utilization;

[0026] 3. Through scientific design and proportioning, active stimulants are preferably selected. Under the dual physical and chemical stimulation modes, the white gelling material of the present invention has high strength and high whiteness. In addition, the product has the unique advantages of low alkali and low shrinkage, and can be better applied to decorative products and large-volume products to avoid efflorescence and cracking. DETAILED DESCRIPTION

[0027] The embodiments of the present invention are described in detail below. The embodiments are implemented on the premise of the technical solution of the present invention, and detailed implementation methods and specific operation processes are given, but the protection scope of the present invention is not limited to the following embodiments.

[0028] Example 1

[0029] A low-carbon high-performance white cementitious material, the raw material components of which are as follows by weight: 63.4% S95 mineral powder, 16% gypsum (mass ratio of anhydrite to phosphogypsum is 1:3), 5% white silicate cement clinker, 5% lithium slag, 10% white filler, and 0.6% composite active activator (mass ratio of nano-hydrated calcium silicate powder to sodium lactate is 1:2).

[0030] Among them, the Hunter whiteness of S95 mineral powder is greater than or equal to 85, and Fe 2 O 3 Content is less than or equal to 0.6%, Al 2 O 3 The content is greater than or equal to 12%.

[0031] Lithium slag is the industrial residue produced by calcining spodumene at 1 000-1 200 ℃ and then using sulfuric acid to produce lithium carbonate. Its chemical components include SiO 2 and Al 2 O 3 , and the total content of the two is greater than 60%.

[0032] The white filler is waste high-temperature white ceramic waste, and its components include SiO 2 、Al 2 O 3 ,CaO.

[0033] A method for preparing a low-carbon, high-performance white gelling material, comprising the following steps:

[0034] Weigh S95 ore powder, gypsum, white silicate cement clinker, lithium slag, white filler and composite active activator according to the above proportions, mix these raw materials evenly, and then put all the raw materials into a full-range planetary ball mill for grinding, set the speed to 300r / min, the ball-to-material ratio to 8:1, the grinding time to 60min, and grind to a specific surface area of ​​800m 2 / kg to obtain low-carbon high-performance white gelling material.

[0035] Example 2

[0036] A low-carbon, high-performance white cementitious material is disclosed. The difference from Example 1 is that the weight percentage of each raw material component is set to: 64.4% of S95 mineral powder, 15% of gypsum (the mass ratio of anhydrite to phosphogypsum is 1:3), 4% of white silicate cement clinker, 4% of lithium slag, 12% of white filler, and 0.6% of composite active activator (the mass ratio of nano-hydrated calcium silicate powder to sodium lactate is 1:2). The low-carbon, high-performance white cementitious material is prepared by the same preparation method as Example 1.

[0037] Example 3

[0038] A low-carbon, high-performance white cementitious material is disclosed. The difference from Example 1 is that the weight percentage of each raw material component is set to: 64.4% S95 mineral powder, 14% gypsum (the mass ratio of anhydrite to phosphogypsum is 1:3), 3% white silicate cement clinker, 3% lithium slag, 15% white filler, and 0.6% composite active activator (the mass ratio of nano-hydrated calcium silicate powder to sodium lactate is 1:2). The low-carbon, high-performance white cementitious material is prepared by the same preparation method as Example 1.

[0039] Comparative Example 1

[0040] Commercially available 525 white cement.

[0041] Comparative Example 2

[0042] The only difference from Example 1 is that the amount of gypsum added is 10%, and the reduced amount is added to the mineral powder.

[0043] Comparative Example 3

[0044] The only difference from Example 1 is that all the gypsum is phosphogypsum.

[0045] Comparative Example 4

[0046] The only difference from Example 1 is that the amount of white Portland cement clinker is 2%, and the reduced amount is added to the mineral powder.

[0047] Comparative Example 5

[0048] The only difference from Example 1 is that no lithium slag is added, and a reduced amount is added to the mineral powder.

[0049] Comparative Example 6

[0050] The only difference from Example 1 is that no white filler is added and a reduced amount is added to the mineral powder.

[0051] Comparative Example 7

[0052] The only difference from Example 1 is that no composite active activator is added, and a reduced amount is added to the mineral powder.

[0053] Comparative Example 8

[0054] The only difference from Example 1 is that the grinding was only performed for 30 min.

[0055] Detailed performance tests were conducted on the above-mentioned Examples 1, 2, 3 and Comparative Examples 1, 2, 3, 4, 5, 6, 7, and 8. Compressive strength, flexural strength, whiteness, setting time, and stability tests were conducted with reference to GB / T2015-2017 "White Portland Cement". In addition, a shrinkage test was conducted using a non-contact bellows shrinkage and expansion tester NELD-CS730. The shrinkage rate was tested from 28 days after final setting according to a ratio of 1:1 between standard sand and cementitious material and a water-cement ratio of 0.4. The PH experiment was conducted by mixing the slurry at a water-cement ratio of 0.4, forming a 100*100*100mm test block, and testing the PH of the initial slurry, the internal core sampling of the 3-day test block, and the internal core sampling of the 28-day test block. The specific test results are shown in Tables 1 and 2.

[0056] Table 1 Example test results

[0057]

[0058]

[0059] Table 2 Comparative Example Test Results

[0060]

[0061]

[0062] It can be seen from Table 1 and Table 2 that Examples 1, 2 and 3 can achieve the performance advantages of high strength, high whiteness, low alkali and low shrinkage within the preferred ratio range of the present invention.

[0063] Comparative Example 1 shows that the white cementitious material of the present invention has higher strength and whiteness, lower pH and shrinkage than Aalborg 52.5 white cement.

[0064] Comparative Example 2 shows that gypsum, as a sulfate activator, provides SO 4 2- The hydration reaction of the cementitious material of the present invention has a significant impact. When the gypsum content is too small, the SO 4 2- The less the amount of hydration reaction, the less the strength of the material will be.

[0065] Comparative Example 3 shows that anhydrite has higher solubility and dissolution rate, and dissociates SO earlier than phosphogypsum. 4 2-It can promote the hydration reaction, shorten the setting time, improve the early strength, and also have a certain impact on the later strength.

[0066] Comparative Example 4 shows that the hydration reaction of the cementitious material of the present invention requires a certain alkalinity. When the amount of clinker is too small, the OH in the solution - The alkalinity is insufficient, the reaction rate and degree are insufficient, resulting in the failure to develop strength in the early and late stages.

[0067] Comparative Example 5 shows that a small amount of lithium slag can promote the hydration reaction of the cementitious material of the present invention, which not only improves the early strength, but also optimizes the hardened slurry structure and improves the later strength.

[0068] Comparative Example 6 shows that the white filler can significantly increase the whiteness of the cementitious material of the present invention, and at the same time has a certain activity. While participating in the reaction, it can be used as a filler to fill pores, increase density, and improve later strength.

[0069] Comparative Example 7 shows that the composite active activator of the present invention can effectively stimulate the activity of mineral powder. The combination of two different activators enables the early and late mineral powders of the material to react to the maximum extent, and a large amount of hydration products are generated, which are interspersed and overlapped with each other to form a dense and high-strength hardened slurry.

[0070] Comparative Example 8 shows that there is a close relationship between the fineness and performance of the cementitious material of the present invention. When the particle size increases, the overall specific surface area of ​​the material decreases, the contact surface for hydration reaction decreases, the generated hydration products decrease, and at the same time, the hydration products cover the unhydrated particles, greatly affecting the strength of the material.

Claims

1. A low-carbon, high-performance white gelling material, characterized by: The raw material components are as follows: S95 mineral powder 50-80%, gypsum 12-20%, white silicate cement clinker 3-6%, lithium slag 1-5%, white filler 10-30%, composite active activator 0.2-0.8% by weight; The Hunter whiteness of the S95 mineral powder is greater than or equal to 85, the Fe2O3 content is less than or equal to 0.6%, and the Al2O3 content is greater than or equal to 12%.

2. A low-carbon, high-performance white cementitious material as described in claim 1, wherein the weight percentage of its raw material components is: S95 mineral powder 60-70%, gypsum 14-16%, white silicate cement clinker 3-5%, lithium slag 3-5%, white filler 10-15%, and composite active activator 0.6-0.8%.

3. A low-carbon, high-performance white gelling material as claimed in claim 1, characterized in that: The gypsum is a mixture of natural anhydrite and chemically impurity-removed white phosphogypsum in a mass ratio of 1:

3.

4. A low-carbon, high-performance white gelling material as claimed in claim 1, characterized in that: The lithium slag is an industrial residue produced by producing lithium carbonate by sulfuric acid method after calcining spodumene at a high temperature of 1000-1200°C. The chemical components include SiO2 and Al2O3, and the total content of the two is greater than 60%.

5. A low-carbon, high-performance white gelling material as claimed in claim 1, characterized in that: The white filler is discarded high-temperature white ceramic waste, and its components include SiO2, Al2O3 and CaO.

6. A method for preparing a low-carbon high-performance white gelling material according to any one of claims 1 to 5, characterized in that: The steps are: Weigh S95 mineral powder, gypsum, white silicate cement clinker, lithium slag, white filler and composite active activator in proportion, mix these raw materials evenly, and then put all the raw materials into a full-range planetary ball mill for grinding, set the speed to 300r / min, the ball-to-material ratio to 8:1, the grinding time to 60min, and grind to a specific surface area of ​​800m 2 / kg to obtain low-carbon high-performance white gelling material.

Citation Information

Patent Citations

  • A kind of ecological type high-strength modified white cement and preparation method thereof

    CN103819105B

  • Production of white cement from industrial waste residue and alkaline residue and its preparation method

    CN108793782B